The Effect of ChatGPT Utilization on Students' Digital Literacy at SMA Negeri 1 2X11 Kayutanam - Aiche Syaqira; Marlini (Darul Yasin Al Sys, 2026)
The rapid development of artificial intelligence (AI), particularly ChatGPT, has transformed learning practices by providing students with immediate access to information and interactive academic support. However, empirical evidence regarding its influence on digital literacy among secondary school students remains limited. This study examined the effect of ChatGPT utilization on the digital literacy of students at SMA Negeri 1 2X11 Kayutanam. A quantitative approach with a descriptive design was employed, involving 82 students selected through simple random sampling from a population of 448 students. Data were collected using questionnaires, supported by interviews and a literature review, and analyzed through descriptive statistics and simple linear regression using SPSS version 25. The findings showed that both ChatGPT utilization and students’ digital literacy were categorized as good. Hypothesis testing demonstrated that ChatGPT utilization had a positive and statistically significant effect on digital literacy (t = 4.558, p < 0.001), accounting for 20.6% of the variance in students’ digital literacy (R² = 0.206). These findings indicate that responsible ChatGPT utilization can contribute to strengthening students’ digital literacy. This study provides empirical evidence regarding the role of generative AI in secondary education and offers practical implications for schools and educators seeking to integrate ChatGPT into learning while promoting critical thinking, information verification, and ethical digital practices.